EVALUASI EFEK ANTIPIRETIK AKAR PAKIS TANGKUR (Polypodium feei METT) PADA MENCIT YANG TERINDUKSI VAKSIN DTP-HB - Hesti Renggana; Isye Martiani; Risa Susanti; Dani Sujana; Zakiah Nur Aeni (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Fever is a state where the body's core temperature rises above normal levels. In healthy adults, the average oral temperature is around 37°C. Fever is not harmful but in certain circumstances this response is undesirable because it interferes with normal activities. The research method used is True Experimental with Posttest Only Control Group Design approach as the research design. The purpose of this study was to assess the antipyretic effect of tangkur fern root on mice induced by DTP-HB vaccine. The results showed that the extract and water fraction of tangkur fern root had antipyretic effects by reducing the fever temperature of mice during the observation time for 240 minutes. Overall, this study proves that the ethanol extract at a dose of 100 mg/kgBB is an effective dose as a candidate for antipyretic drugs.